The Ability of Fluoresncent Pseudomonad to Produce Cyanide Acid - Putri Andam Dewi; Linda Advinda (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Fluorescent pseudomonads are a group of bacteria derived from plant rhizosphere and have the ability to produce antimicrobial compounds, namely cyanide acid. This study aims to obtain fluorescent pseudomonad isolates that can produce cyanide acid. The fluorescent pseudomonad isolates used were isolate Pf31 (derived from the rhizosphere of the longan plant), Pf32 (derived from the rhizosphere of the cassava plant), Pf33 (derived from the rhizosphere of the guava plant), Pf35 (derived from the rhizosphere of the galangal plant), Pf36 (derived from the rhizosphere of the guava plant). red ginger), Pf37 (derived from the rhizosphere of the Alocasia plant), Pf38 (derived from the rhizosphere of the celery plant), Pf39 (derived from the rhizosphere of the turmeric plant), and Pf40 (derived from the rhizosphere of the Oxalis plant). This research is a descriptive study conducted by detecting the ability of fluorescent pseudomonads to produce cyanide. The results of this study showed that 4 isolates produced cyanide, namely Pf31, Pf37, Pf38, and Pf39. Pf31 and Pf37 isolates produced the highest cyanide acid, indicated by a brick red color on the filter paper and Pf 32, Pf33, Pf35, Pf 36 and Pf40 isolates did not produce cyanide acid with the filter paper remaining yellow.